ANALISIS PENGARUH CAPITAL INTENSITY, KEPEMILIKAN INSTITUSIONAL, DEBT TO ASSET RATIO (DAR) DAN RETURN ON ASSETS (ROA) TERHADAP EFFECTIVE TAX RATE (ETR) PADA PERUSAHAAN SEKTOR PROPERTI UTAMA YANG TERDAFTAR DI BEI PERIODE 2016 -2019 - Chytia Chytia; Bayu Laksma Pradana (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2021)
The purpose of this study was to determine the effect of capital intensity, institutional ownership, debt to asset ratio (DAR), and return on assets (ROA) on the effective tax rate (ETR). This study uses secondary data in the form of financial reports that have been audited by auditors, where this data is obtained from the official website of the Indonesia Stock Exchange (idx.co.id). Testing in this study was assisted by using the SPSS 25 program by using multiple linear regression analysis hypothesis testing. The sample technique used in this research is purposive sampling method. The criteria taken by the author in this study are companies engaged in the property sector and have complete financial reports for 4 (four) years, from 2016-2019. The sample taken is 25 property companies for 4 years, which means that it has a total sample of 100 companies. From the existing sample, the classical assumption test was carried out consisting of the normality test, autocorrelation test, multicollinearity test, and heteroscedasticity test along with the regression coefficient similarity test consisting of the t test, F test, and the coefficient of determination (R2) test.